2018
DOI: 10.1074/jbc.ra118.002639
|View full text |Cite
|
Sign up to set email alerts
|

Brain microvascular endothelial cells exhibit lower activation of the alternative complement pathway than glomerular microvascular endothelial cells

Abstract: Atypical hemolytic uremic syndrome (aHUS) and bone marrow transplantation-associated thrombotic microangiopathy (TA-TMA) are associated with excessive activation of the alternative complement pathway (AP) and with severe renal, but rarely cerebral, microvascular damage. Here, we compared AP activation and regulation in human glomerular and brain microvascular endothelial cells (GMVECs and BMVECs, respectively) unstimulated or stimulated by the proinflammatory cytokine, tumor necrosis factor (TNF). Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 80 publications
1
40
1
Order By: Relevance
“…These parameters are, respectively, an acute phase protein and a surrogate marker of dehydration and have been repeatedly associated with adverse outcomes in STEC-HUS patients ( 43 45 ). In our study, however, these laboratory markers did not significantly affect the development of CNS involvement in the multivariate model, probably due to the key role of alternative pathway activation in the onset of thrombotic microangiopathy onto brain microvascular endothelial cells ( 46 , 47 ).…”
Section: Discussioncontrasting
confidence: 80%
“…These parameters are, respectively, an acute phase protein and a surrogate marker of dehydration and have been repeatedly associated with adverse outcomes in STEC-HUS patients ( 43 45 ). In our study, however, these laboratory markers did not significantly affect the development of CNS involvement in the multivariate model, probably due to the key role of alternative pathway activation in the onset of thrombotic microangiopathy onto brain microvascular endothelial cells ( 46 , 47 ).…”
Section: Discussioncontrasting
confidence: 80%
“…Exploring the mRNA expression for Cfh in the kidney showed that the expression was identical in the WT and hepatoFH −/− mice and was not affected by PHZ injection (Figure 5B). Exploring of FH staining in mouse kidney has been tricky and previous studies failed to detect it despite the clear evidence for mRNA production by various renal cell populations (26)(27)(28)(29)(30)(31). The reason for this lack of staining in previous studies vs. the positive staining detected here is unclear and is likely related to the experimental conditions.…”
Section: Fh Is Present In the Mouse Kidneymentioning
confidence: 56%
“…Recent investigations have reported that the vascular endothelium also plays an important role in modulating the activation and differentiation of B‐ and T‐cells 3‐5 . The expression of the complement anaphylatoxin receptors C3aR and C5aR1 has been documented in several different types of vascular endothelium from tissues and cells from human as well as from other species 48‐51 . However, their significance and overall impact on endothelial cellular function remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%